Estimatian of individual and maternal heterosis and genetic parameters for production traits in holstein-indigenous crossbred cows of Iran - Moradi-Shahrbabak, M. (Malaysian Society of Animal Production, 2014)
This study used 8551 and 7665 milk production records derived from 1314 and 1178 crossbed (CB) and indigenous (IND) cows for evaluation. Records were gathered during 1991 to 2000 in Isfehan province by the Iranian Animal Breeding Center (IABC). Data were analyzed using single and repeated record animal models with derivative- free restricted maimum likelihood (DF-REML) method. The adjusted means for milk and fat yield in FICB, IND and first backcross to Holstein (BC1H) cows were 1531.9 (37.1) and 60.3 (1.4), 2228.1 (54) and 77 (1.9), and 2662.3 (120.7) and 103.3 (4.4), respectively. Results showd that lactation, herd, and year-season factors affected milk and fat yield significantly. Cows with 75% of Holstein genes had higher least squared means for milk and fat yield than the others. The effects of Holstein breed, individual and maternal heterosis were estimated 20.86, 11.85, and 5.05 kg for milk yield, and 0.172, 0414, and 0.293 kg for fat yield, respectively. Estimated heritability and repeatability were 0.37 (0.03) and 0.33 (0.005), 0.35 and 0.43 (0.03) and 0.37 (0.02), and 0.38 for milk and fat yield, respectively, in single and repeated record models.